Protein Acetylation Increased Risk of Fibrosis-Related Liver Cancer. (23rd January 2023) - Li, Yuan; Wang, Yanyan; Song, Zhaopu; Lu, Kai; Chen, Wenwen; Ma, Yuanyuan; Ding, Hui; Li, Xiaofang; Li, Xiuling; Sun, Suofeng
Abstract : Objective . The occurrence of liver fibrosis and fibrosis-related liver cancer is the reason for the increase in morbidity and mortality worldwide. Transforming growth factor- β 2 (TGF- β 2) is an important mediator of chronic liver fibrosis. This study aims to find the molecular mechanism that mediates HBV infection and induces TGF- β 2 and verifies that CREB binding protein acetylation mediates HBV infection and induces TGF- β 2 expression. Methods . The acetylated proteins were extracted from HepG2-NTCP cells and HBV-infectedHepG2-NTCP cells. The acetylated proteins were screened by modification enrichment technology and database search. Protein annotation, motif analysis of modification sites, and protein function enrichment analysis of these proteins were performed to roughly clarify the location and function of these acetylated modification proteins in cells. Acylated proteins enriched in the TGF- β pathway were obtained by KEGG pathway enrichment analysis. The effect of the selected acetylated modification protein on the TGF- β pathway was verified by experiments, that is, the target protein gene was knocked out by siRNA, and the expression level of the TGF- β 2 was detected by qRT-PCR. Results . Proteins were extracted from HepG2-NTCP cells and HepG2-NTCP cells infected with HBV, and differential acetylation modification proteins were screened. The target protein CREB binding protein was screened by modification enrichment technology and database search. The aggregation analysis of TGF- β pathway showed that CREB binding protein was acetylated at amino acid positions 434 and 439, and enriched in the TGF- β signaling pathway. siRNA targeting CREB binding protein was transfected, and the expression of TGF- β 2 in cells was detected by qRT-PCR and western blot, respectively. It was verified that HBV infection-inducedCREB-binding protein acetylation regulated the high expression of TGF- β 2. Conclusion . After HBV infection, CREBBP acetylation was up-regulated, which promoted the high expression of TGF- β 2.